Different dynamics of Usutu virus infections in Austria and Hungary, 2017–2018 - Weidinger, Pia (Transbound Emerg Dis, 2019)
Usutu virus (USUV), a mosquito‐borne flavivirus closely related to West Nile virus, emerged in Austria in 2001, when it caused a considerable mass‐mortality of Eurasian blackbirds. Cases in birds increased until 2003 and quickly declined thereafter, presumably due to developing herd immunity. Since 2006, no further cases were recorded, until two blackbirds were tested positive in 2016. In Hungary, USUV first appeared in 2005 and has caused only sporadic infections since then. Initially, the only genetic USUV lineage found across both countries was Europe 1. This changed in 2015/2016, when Europe 2 emerged, which has since then become the prevalent lineage. Due to dispersal of these strains and introduction of new genetic lineages, USUV infections are now widespread across Europe. In 2009, the first cases of USUV‐related encephalitis were described in humans, and the virus has been frequently detected in blood donations since 2016. To monitor USUV infections among the Austrian wild bird population in 2017/2018, 86 samples were investigated by RT‐PCR. In 67 of them, USUV nucleic acid was detected (17 in 2017, 50 in 2018). The majority of succumbed birds were blackbirds, found in Vienna and Lower Austria. However, the virus also spread westwards to Upper Austria and southwards to Styria and Carinthia. In Hungary, 253 wild birds were examined, but only six of them were infected with USUV (five in 2017, one in 2018). Thus, in contrast to the considerable increase in USUV‐associated bird mortality in Austria, the number of infections in Hungary declined after a peak in 2016. Except for one case of USUV lineage Africa 3 in Austria in 2017, Europe 2 remains the most prevalent genetic lineage in both countries. Since USUV transmission largely depends on temperature, which affects vector populations, climate change may cause more frequent USUV outbreaks in the future.